Self Care and Blood Pressure Control Education Using Audio Visual for Self Management in Hypertension: Edukasi Perawatan Diri dan Pengendalian Tekanan Darah Menggunakan Media Audio Visual untuk Manajemen Diri pada Hipertensi - Indriyati, Fira; Sukesih, Sukesih; Kartikasari, Fitriana (Indonesian Journal of Innovation Studies, 2025)
Background: Hypertension remains a major public health challenge globally and in Indonesia, with suboptimal self management contributing to uncontrolled blood pressure and related complications. Specific background: Health education focusing on self care and blood pressure control is essential; however, conventional delivery methods often provide limited support for patient understanding and engagement. Knowledge gap: Empirical evidence on audio visual–based health education addressing self care and blood pressure control within primary health care settings is still limited. Aims: This study aimed to examine self management outcomes following self care and blood pressure control education delivered using audio visual media. Results: A quasi-experimental control group pretest–posttest design involving 60 hypertension patients demonstrated substantial improvements in self management scores in the intervention group, while only minor changes were observed in the control group, with statistically significant differences between groups. Novelty: This study introduces a structured audio visual health education approach integrating self care and blood pressure control tailored for community health centers. Implications: Audio visual–based health education represents a feasible strategy to support self management practices among hypertension patients in primary health care services. Highlights • Audio visual health education addresses self care and blood pressure control in hypertension. • Self management scores showed clear differences between intervention and control groups. • Community health centers provide a practical setting for audio visual education delivery. Keywords Hypertension, Health Education, Audio Visual, Self Management, Primary Health Care